Correlation Theory A.V. Dicey Perspective of the Rule of Law in Indonesia: Correlation Theory A.V. Dicey Perspective of the Rule of Law in Indonesia - I Nyoman Prabu Buana Rumiartha (Universitas Bali Dwipa, 2022)
The rule of law is not only subject to the rule of law, but also includes ethical (moral) values, good norms in this case contained in the law or as a civilization that lives in society for the public interest which has an impact on society. There is equality before the law, in this case everyone regardless of their position and class in society is subject to the same law. Likewise, state functionaries are subject to the same laws as those that apply to ordinary people. Law which is a series of regulations and or laws and regulations that give birth to state institutions and or government agencies that have their respective authorities granted by the laws and regulations, where such authority and power cannot be used outside the legal corridor. This is because it must be subject to the principle of equality before the law. Based on this, it is worth understanding the correlation between the theory of A.V. Dicey perspective of the rule of law in Indonesia on Pancasila and the Constitution.